On an Inequality of Diananda—Part IV - Peng Gao (International Journal of Mathematics and Mathematical Sciences)
We extend the results in parts I–III on certain inequalities involving the weighted power means as well as the symmetric means. These inequalities can be largely viewed as concerning the bounds for ratios of differences of means and can be traced back to the work of Diananda.